Experimental identification of nonlinear coupling between (intermediate, small)-scale microturbulence and an MHD mode in the core of a superconducting tokamak. (1st November 2017) - Sun, P.J.; Li, Y.D.; Ren, Y.; Zhang, X.D.; Wu, G.J.; Xu, L.Q.; Chen, R.; Li, Q.; Zhao, H.L.; Zhang, J.Z.; Shi, T.H.; Wang, Y.M.; et al.
Abstract: In this paper, we present clear experimental evidence of core region nonlinear coupling between (intermediate, small)-scale microturbulence and an magnetohydrodynamics (MHD) mode during the current ramp-down phase in a set of L-mode plasma discharges in the experimental advanced superconducting tokamak (EAST, Wan et al (2006 Plasma Sci. Technol .8 253)). Density fluctuations of broadband microturbulence ( k ⊥ ρ i ∼ 2 − 5.2 ) and the MHD mode (toroidal mode number m = − 1, poloidal mode number n = 1 ) are measured simultaneously, using a four-channel tangential C O 2 laser collective scattering diagnostic in core plasmas. The nonlinear coupling between the broadband microturbulence and the MHD mode is directly demonstrated by showing a statistically significant bicoherence and modulation of turbulent density fluctuation amplitude by the MHD mode.